Contribucion al estudio de la guayaba coronilla, Psidium friedrichsthalianum Beng-Niedenzu - Carabali, A.=700 1 Libreros V,J.; Muñoz F, J.E.; De la Cruz A, G.A.
(Es, En)
Ilus., 10 ref.
Keywords: PSIDIUM; COLECCION DE SEMILLAS; EVALUACION; TIEMPO; REMOJO; ALMACENAMIENTO DE SEMILLAS; GERMINACION; SUPERFICIE FOLIAR; FENOLOGIA; COLOMBIA; PSIDIUM FRIEDRICHáTHALIANUM; GUAYABA CORONILLA; ACTA AGRONOMICA